Analysis of Soet Emissions using Diesel - Methanol (CH3OH) Mixture on L-300 Vehicles - Langgeng Asmoro; Reza Yoga Anindita; Aris Budi Sulistyo; Rahmat Ahmad (Jurnal Teknologi Transportasi dan Logistik, 2023)
In this research, it is intended to identify the concentration of soot in the exhaust emissions of the L-300 diesel engine by adding an additional substance in the form of methanol CH3OH. The research method in this study used an experimental method with the help of a smoke tester used to test the soot concentration in exhaust emissions of diesel motorized vehicles. The experiment was carried out at night using different mixtures and where each mixture will be carried out 8 times to collect data. Experiments used a smoke tester to test soot emissions on: fuel not mixed with methanol additive (M0D100), 5% methanol mixture (M5D95), 10% methanol (M10D90), 15% methanol mixture (M15D85). After carrying out the research and data processing, it was obtained that the M0D100 mixture had a soot emission concentration of 36.52%. The M5D95 mixture decreased the concentration of exhaust emissions to 31.05%. Then in the M10D90 mixture, the soot emission concentration decreased to 27.17%. whereas in the M15D85 mixture the soot concentration increased to 33.76%.